THE IMPACT OF GLOBAL SYMBOLIC-VALUE ORIENTATION AND SUBJECTIVE KNOWLEDGE ON POSITIVE ELECTRONIC WORD OF MOUTH WITH GENERAL ATTITUDE TOWARDS LOCAL BRANDS - Budiono, Sidik; Viola, Viola (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Consumers tend to buy and use global or international fashion products due to the symbolic values orientation that the global fashion products own in general. So will consumers still buy and wear them nowadays while the stereotypes of people using local brands is not as valuable as if they’re wearing global or international fashion brands? This study examined the effects of global symbolic-value orientation, subjective knowledge, and attitude on positive electronic word of mouth (eWOM) towards local brands in the fashion product domain. The study examined these relationship in the generation Z consumers with 240 total respondents. Also, the study draws on cultural identity theory and eWOM concept. Data was collected through an online survey (Google Form) in the JABODETABEK region. The study raised popular local brands that everyone in Indonesia and the author knows in general, as well as the local brands that respondents knew and wrote in the questionnaire as well. Objective : 1) To know whether global symbolic-value orientation has influence towards positive eWOM. 2) To know whether subjective knowledge has influence towards positive eWOM. 3) To know whether general attitude towards local brands has influence towards positive eWOM. 4) To know how global symbolic-value orientation have influence on general attitude towards local brands. 5) To know how subjective knowledge have influence on general attitude towards local brands. Methodology: Quantitative with descriptive correlational method. The data were gathered through purposive sampling.